Anaerobe treatment of organicwaste - Voytovych І.G. (Forestry, Forest, Paper and Woodworking Industry, 2019)
The problems what it is possible to solve with helpe of biogas technology: power industry; agricultural; ecological; social were named. The type of raw materials which was investigated from 1993 y. Into laboratory of UNFU on suitability to receive of biogas were named. The technological factors that influence on process obtaining of biogas ware indicated and occasion from experience functioning of plant when don’t observe to form of biogas were named. It is established that the processing of organic waste without oxygen access from the air is a highly efficient way of obtaining quality organic fertilizers; environmentally friendly energy, which is biogas; reducing environmental pollution and improving the social conditions of residets, especially rural populations. It is recommended for installation in each rural yard where organic, small, family-type biogas plants accumulate up to 20 m3 of organic waste. It is substantiated that after being in biohumus plants, organic waste acquires better characteristics of fertilizers. It is estimated that small biohumus plants can generate enough biogas for their own needs.